"THE GREAT FUTURE - UZBEKISTAN'S DEVELOPMENT STRATEGY" - Azizova Dilnoza Adham qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the further development of political, trade, economic, cultural and humanitarian ties of Uzbekistan with Asian countries.